Patients With Ankylosing Spondylitis Are Associated With High Risk of Fibromyalgia: A Nationwide Population-Based Cohort Study - Gau, Shuo-Yan; Lee, Yung-Heng; Tsou, Hsi-Kai; Huang, Jing-Yang; Chen, Xinpeng; Ye, Zhizhong; Wei, James Cheng-Chung (Frontiers in Medicine, 2021)
Objectives: The main purpose of this retrospective cohort study was to provide an evaluation of Ankylosing spondylitis (AS) patients' fibromyalgia risk in different age and sex subgroups by analyzing large study samples. Methods: Datasets from the National Taiwan Insurance Research Database (NHIRD) were retrieved in this retrospective cohort study. This study was approved by the Institutional Review Board of Chung Shan Medical University (IRB permit number CS15134). Within the Longitudinal Health Insurance Database (LHID), and the subset of NHIRD, we identified AS patients to explore the risk of further fibromyalgia. The exposure cohort included patients with newly-diagnosed AS (ICD-9-CM:720.0) during 2000–2013. After 1:4 age-sex matching and 1:2 propensity score matching, and adjusting potential confounders, individuals without AS were identified as a comparison cohort. The adjusted hazard ratio of subsequent development of fibromyalgia in people with AS was evaluated. Further stratification analyses of different ages and genders were then undertaken to validate the results. Results: In total, 17 088 individuals were included in the present study, including 5,696 patients with AS and 11,392 individuals without AS. Respective incidence rates (per 1,000 person-months) of fibromyalgia was 0.52 (95% CI, 0.46–0.59) in the AS cohort and 0.39 (95% CI, 0.35–0.44) in the non-AS cohort. Compared with the non-AS cohort, aHR of developing fibromyalgia was 1.32 (95% CI, 1.12–1.55) in people with AS. This association was consistent in both statistical models of 1:4 age–sex matching and 1:2 propensity score matching. Conclusion: Patients with AS were associated with a higher risk of fibromyalgia, especially those over 65 years old. In managing patients with AS, clinicians should be aware of this association, which could impact diagnosis, disease activity evaluation, and treatment.